The girl in the woods eaudiobook - Olsen, Gregg (Waterman and Stark, 2015)
A schoolgirl found it on a nature hike. A severed human foot wearing pink nail polish. A gruesome but invaluable clue that leads forensic pathologist Birdy Waterman down a much darker trail—to a dangerous psychopath whose powers of persuasion seem to have no end. Only by teaming up with sheriff's detective Kendall Stark can Birdy hope to even the odds in a deadly game. It's a fateful decision the killer wants them to make. And it's the only way Birdy and Kendall can find their way to a murderer who's ready to kill again . . .